Work Motivation and Environment Effects on Maritime Warehouse Performance - Adnan Genawi; M. Jhon; N. Achmad Jabrial; Ishak Traindra; Arif Supriatna (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This qualitative research investigates the influence of work motivation and work environment on employee performance within PT Yusen Logistic Indonesia's warehouse division. Through comprehensive interviews with maritime professionals, educators, and industry experts, this study addresses critical gaps in understanding workforce dynamics in maritime logistics operations. The research employed thematic analysis of semi-structured interviews with 45 participants across three stakeholder groups: operational staff, maritime educators, and industry professionals. Findings reveal that intrinsic motivation factors, particularly career development opportunities and safety recognition, demonstrate stronger correlation with sustained performance than monetary incentives. Work environment quality, including infrastructure adequacy and shift management, serves as a significant moderator affecting motivation–performance relationships. In addition, this research highlights that supportive leadership and open communication further strengthen employee engagement and commitment in high-pressure warehouse operations. Respondents consistently emphasized the importance of aligning organizational goals with individual career aspirations, particularly in a sector where safety and efficiency are paramount. The study also identifies that investment in ergonomic facilities, digital monitoring systems, and structured training programs reduces fatigue and error rates, thus promoting both productivity and safety compliance. The implications extend beyond company-level management to broader maritime education and policy-making. The integration of motivational strategies into vocational curricula can better prepare graduates for the realities of port and logistics operations. Moreover, the findings contribute to developing sustainable logistics practices that balance efficiency, employee well-being, and long-term organizational competitiveness. Overall, the research provides evidence-based recommendations for maritime vocational training programs, human resource management, and port operations strategies in Indonesia’s rapidly growing logistics sector.